Silver Anniversary: 25 Editions of the IMIA Yearbook - Lehmann, Christoph U.; Jaulent, Marie-Christine; Séroussi, Brigitte (Yearbook of Medical Informatics, 2016)
Objectives: To provide an editorial introduction into the special 25th anniversary edition of the IMIA Yearbook of Medical Informatics with discussion of the significance of the Yearbook, past and current editorial teams, and a look into the future. Methods: A brief overview of the 2016 anniversary edition of the Yearbook allows for a discussion of the significance and value of the Yearbook to the Biomedical Informatics community as well as a review of changes in Yearbook team and format over time. Results: The IMIA Yearbook celebrates its 25th edition bearing witness to the quality of the IMIA brand, the Yearbook content, as well as to the dedication of and the inordinate amount of labor from the authors and editors of the Yearbook. Editorial teams are to be applauded for their hard work and for their foresight in steering the Yearbook from a paperback to an open access online publication. The special edition provides reviews of past editorials with the knowledge of today.Conclusions: The IMIA Yearbook celebrates a remarkable milestone providing a testament to the maturity of the Biomedical Informatics field. Informaticians across the world are encouraged to thank past editorial teams and celebrate with IMIA.
Keywords: International Medical Informatics Association; Yearbook; silver anniversary; biomedical informatics